Peningkatan Kemampuan Literas Numerasi Siswa Melalui Pendekatan Saintifik di SMP Swasta PAB 2 Helvetia - Syahrina Anisa Pulungan; Fira Astika Wanhar (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research is classroom action research which aims to improve students' numeracy literacy skills through a scientific approach carried out in class VIII PAB 2 Helvetia in the even semester of the 2022/2023 academic year with a total of 32 students. This research was conducted in three cycles. Data collection was carried out using the results of students' numeracy ability tests. The data obtained was collected and analyzed using descriptive statistical analysis, where the indicator of the success of this research was an increase in the N-Gain pretest posttest value of students' numeracy abilities during each learning cycle. The research results showed that in the first cycle, the N-Gain value of students' numeracy abilities was 0.15 in the low category, in the second cycle it increased to 0.84 in the high category and in the third cycle it increased to 0.87 in the high category. Thus it can be concluded that the application of a scientific approach is able to improve students' numeracy skills